Zero fluoroscopy catheter ablation for atrial fibrillation: a systematic review and meta-analysis - Debreceni, Dorottya; Janosi, Kristof; Bocz, Botond; Turcsan, Marton; Lukacs, Reka; Simor, Tamas; Antolič, Bor; Vamos, Mate; Komocsi, Andras; Kupo, Peter (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Catheter ablation for atrial fibrillation (AF) is the most frequently performed cardiac ablation procedure worldwide. The majority of ablations can now be performed safely with minimal radiation exposure or even without the use of fluoroscopy, thanks to advances in 3-dimensional electroanatomical mapping systems and/or intracardiac echocardiography. The aim of this study was to conduct a meta-analysis to compare the effectiveness of zero fluoroscopy (ZF) versus non-zero fluoroscopy (NZF) strategies for AF ablation procedures. Methods: Electronic databases were searched and systematically reviewed for studies comparing procedural parameters and outcomes of ZF vs. NZF approaches in patients undergoing catheter ablation for AF. We used a random-effects model to derive the mean difference (MD) and risk ratios (RR) with a 95% confidence interval (CI). Results: Our meta-analysis included seven studies comprising 1,593 patients. The ZF approach was found to be feasible in 95.1% of patients. Compared to the NZF approach, the ZF approach significantly reduced procedure time (mean difference (MD): -9.11 min (95% CI: -12.93 to -5.30 min; p<0.01)), fluoroscopy time (MD: -5.21 min (95% CI: -5.51 to -4.91 min; p<0.01)), and fluoroscopy dose (MD: -3.96 mGy (95% CI: -4.27 to -3.64; p<0.01)). However, there was no significant difference between the two groups in terms of total ablation time (MD: -104.26 sec (95% CI: -183.37 to -25.14; p=0.12)). Furthermore, there was no significant difference in the acute (risk ratio (RR): 1.01, 95% CI: 1.00–1.02; p=0.72) and long-term success rates (RR: 0.96, 95% CI: 0.90–1.03; p=0.56) between the ZF and NZF methods. The complication rate was 2.76% in the entire study population and did not differ between the groups (RR: 0.94, 95% CI: 0.41–2.15; p=0.89). Conclusion: The ZF approach is a feasible method for AF ablation procedures. It significantly reduces procedure time and radiation exposure without compromising the acute and long-term success rates or complication rates.